High-Temperature Oxidation of the 304/6061 Welding–Brazing Joint and Its Effects on Corrosion Characteristics - Ruilin Liu; Yunqi Liu; Hongming Liu; Yuanxing Li; Hui Chen; Zongtao Zhu (Applied Sciences, 2024)
Laser–MIG hybrid welding–brazing was used to weld 304 stainless steel and 6061-T6 aluminum alloy with a thickness of 2 mm. The microstructure, morphology, chemical composition and corrosion behavior of the samples after high-temperature oxidation were investigated. The results reveal that the 304/6061 dissimilar joint had a thicker intermetallic compound layer (7–8 μm) during high-temperature oxidation (HTO) treatment than the sample without HTO treatment (2–3 μm). The oxide film thickness of the 6061 side of the weld joint treated by HTO (2401 nm) increased compared to the samples (181.1 nm) without HTO treatment. Unlike other metals treated by high-temperature oxidation, the high-temperature treatment process in this paper can reduce the corrosion resistance of the base metal and dissimilar joints, and the sequence of the corrosion current density was weld (HTO) >weld>6061 (HTO) >6061>304 (HTO) >304.